Strategi Pengembangan Kerjasama Perpustakaan Uinsu dengan Perpustakaan Umsu Dalam Upaya Meningkatkan Layanan Perpustakaan - Yusniah Yusniah; Ahmad Fauzi; Ratih Ramadhan; Rahmatullaily Sitorus; Risky Mulyadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Library services need to always be improved so that visitors feel comfortable and their information needs are met by visiting the library. In order to realize excellent library services, library collaboration is important to do in improving service quality. The North Sumatra State Islamic University Library is a university library that has collaborated with several university libraries, both university libraries in North Sumatra and those outside North Sumatra. However, the one that most often carries out collaboration activities with the UINSU library is the University of Muhammadiyah Sumatra Utara (UMSU) library. The strategy for developing cooperation between the library of the State Islamic University of North Sumatra and the University of Muhammadiyah Sumatra Library consists of developing human resources, resource sharing, preparing for accreditation, collections, and information technology. Keywords: Library Collaboration, Library service